Acrometastasis as fi rst sign of adenocarcinoma of the lung - URAKÇI, Zuhat; EBİNÇ, Senar and KÜÇÜKÖNER, Mehmet and MORKUZU, Suat and COŞKUN, Özge YAMAN and ORUÇ, Zeynep and SEZGİN, Yasin and BİLEN, Erkan and KARHAN, Oğur and AKDENİZ, Nadiye and; l. (Archives of Case Reports, 2020)
Lung cancer is a major cause of morbidity and mortality worldwide. Metastasis can be seen in many organs in advanced-stage disease. Acral metastasis rate in cancer is quite low. However, because of the direct opening of the arterial circulation, the risk of acral metastasis stem from lung cancer is higher than any other cancers. Although the mechanism is not known exactly, acral metastases occur in dominant extremities. Here, we present a case with lung adenocarcinoma metastasis of the left hand in the second phalanx. We presented this case which is rarely seen in the literature to emphasize acral metastases.